Kombinasi Pupuk N, P, K Denganpupuk Organik Granul (Pog) Untuk Meningkatkan P-Tersedia Dan Serapan Hara Jagung (Zea mays L.) Pada Typic Eutrudept - Hermawan, Mega Kartika; Sofyan, Emma Trinurani; Machfud, Yuliati (Jurnal Agrotek Indonesia, 2018)
Balanced fertilizing is a site-specific nutrient management concept that takes into consideration the ability of soils to provide nutrients naturally and nutrient recovery previously uptaked by plants. The concept is a response to the various negative impacts caused by intensive and continuous inorganic fertilizing. This study aims to determine the combinantion of N, P, K fertilizer with Granular Organic Fertilizer (POG) that can give the best effect on available phosphate in soil, nutrient uptake and the growth of maize (Zea Mays L.)in Typic Eutrudept. The research used rendomized block design (RBD) with ten treatments and three replications. The results showed combination of ½ N, P, K + 1 POG gave significant effect to increase available-P and nutrient uptake of maize (Zea Mays L.). Keywords: Granular Organic Fertilizer, Maize, Nutrient Uptake, Typic Eutrudept.